2011
DOI: 10.1073/pnas.1108616108
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular reduction of uranium via Geobacter conductive pili as a protective cellular mechanism

Abstract: The in situ stimulation of Fe(III) oxide reduction by Geobacter bacteria leads to the concomitant precipitation of hexavalent uranium [U(VI)] from groundwater. Despite its promise for the bioremediation of uranium contaminants, the biological mechanism behind this reaction remains elusive. Because Fe(III) oxide reduction requires the expression of Geobacter 's conductive pili, we evaluated their contribution to uranium reduction in Geobacter sulfurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
239
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 221 publications
(253 citation statements)
references
References 52 publications
10
239
0
1
Order By: Relevance
“…Genetic studies in the model representative Geobacter sulfurreducens (GS) have provided insights into how the cells assemble the GS pilin into a conductive fibre. However, little is known about how respiratory electrons are discharged through the T4P, partly because mutations that inactivate key electron carriers of the cell envelope, whether the T4P or c‐Cyts, are often pleiotropic (Kim et al ., 2005, 2006; Kim and Lovley, 2008; Cologgi et al ., 2011; Richter et al ., 2012; Steidl et al ., 2016). As a result, compensatory effects are often observed that can mask the true phenotype of the mutants.…”
Section: A Nanowire Pathway For Metal Reductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Genetic studies in the model representative Geobacter sulfurreducens (GS) have provided insights into how the cells assemble the GS pilin into a conductive fibre. However, little is known about how respiratory electrons are discharged through the T4P, partly because mutations that inactivate key electron carriers of the cell envelope, whether the T4P or c‐Cyts, are often pleiotropic (Kim et al ., 2005, 2006; Kim and Lovley, 2008; Cologgi et al ., 2011; Richter et al ., 2012; Steidl et al ., 2016). As a result, compensatory effects are often observed that can mask the true phenotype of the mutants.…”
Section: A Nanowire Pathway For Metal Reductionmentioning
confidence: 99%
“…The conductive T4P are also the primary mechanism for the reduction of the uranyl cation (UO 2 2+ ) (Cologgi et al ., 2011). The fibres bind the soluble cation extracellularly and discharge respiratory electrons to reduce the U(VI) to a mononuclear U(IV) mineral phase (Cologgi et al ., 2011).…”
Section: A Nanowire Pathway For Metal Reductionmentioning
confidence: 99%
See 3 more Smart Citations